Catalyst coating film, preparation method thereof, membrane electrode and application
By stacking the catalyst coated film on the release film, the problems of proton exchange membrane swelling and uneven catalytic layer structure in traditional membrane electrode preparation are solved, and the high flatness, uniformity and excellent electrochemical properties of the membrane electrode are achieved.
Patent Information
- Application Number
- CN202311252345.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-03-28
AI Technical Summary
In the traditional fuel cell membrane electrode preparation method, the proton exchange membrane is prone to swelling and wrinkling, resulting in uneven surface structure of the catalytic layer, and the hot pressing process will destroy the initial structure of the catalytic layer.
By adopting a method of preparing a catalyst coated film, the problems of uniformity and binding force of the catalytic layer are solved by preparing the first catalytic layer, the first resin layer, the ePTFE microporous film, the second resin layer and the second catalytic layer on the release film, and by laminating and removing the release film, the uniformity and binding force of the catalytic layer are solved.
The surface flatness of the membrane electrode is achieved, with excellent electrochemical performance, and the problems of swelling and structural inhomogeneity of the proton exchange membrane are avoided.
Smart Images

Figure CN119725562A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of fuel cell technology, and in particular to a catalyst coated membrane and a preparation method thereof, a membrane electrode and applications. Background Art
[0002] A fuel cell is a device that directly converts the chemical energy of fuel and oxidant into electrical energy through electrochemical reactions. Fuel cells have the characteristics of high energy conversion efficiency, no exhaust gas emissions, and high material recyclability, which is conducive to coping with energy crises. Currently, they are increasingly used in transportation, fixed power stations, and backup power supplies, and their prospects are very good.
[0003] The membrane electrode assembly is the core component of the proton exchange membrane fuel cell, and its cost accounts for one-third of the total cost. There are two ways to prepare the membrane electrode. The first way is to directly coat the catalyst layer on the proton membrane to form a catalyst coated membrane (CCM, Catalyst Coated Membrane), and then bond the CCM with the gas diffusion layer (GDL) to prepare a membrane electrode. The second way is to directly coat the catalyst slurry on the GDL to prepare a gas diffusion electrode (GDE) and then combine it with the proton exchange membrane.
[0004] The CCM prepared by the coating method will have the effect of reducing internal resistance and improving performance. However, the proton exchange membrane in the traditional coating method is prone to swelling and wrinkling after being separated from the protective membrane. It is difficult to control the uniformity of the surface structure when coating the second catalytic layer. The second catalytic layer can be prepared on the release film by thermal transfer and then heat transferred to the proton exchange membrane, but a large amount of the second catalytic layer still remains on the release film, and hot pressing will destroy the initial structure of the first catalytic layer. Summary of the invention
[0005] Based on this, the present application provides a catalyst coated membrane and a preparation method thereof, a membrane electrode and an application thereof. The preparation method of the catalyst coated membrane of the present application solves the swelling and shrinkage problems of the proton exchange membrane during the continuous coating process, avoids the problems of poor structural uniformity and shedding of the first catalytic layer and the second catalytic layer, and the first catalytic layer is tightly bonded to the surface of the first resin layer, so that the membrane electrode surface has high flatness, good uniformity and excellent electrochemical performance.
[0006] In a first aspect of the present application, a method for preparing a catalyst coated membrane is provided, wherein the catalyst coated membrane comprises a first catalyst layer, a first resin layer, an ePTFE (expanded polytetrafluoroethylene) microporous membrane, a second resin layer and a second catalyst layer stacked in sequence; the method for preparing the catalyst coated membrane comprises the following steps:
[0007] Preparing the first catalytic layer on one side surface of the release film;
[0008] Prepare the first resin layer on the surface of the ePTFE microporous membrane;
[0009] Laminating and pressing the first resin layer and the first catalyst layer;
[0010] Prepare the second resin layer on the surface of the ePTFE microporous membrane away from the first resin layer;
[0011] preparing the second catalytic layer on the surface of the second resin layer away from the ePTFE microporous membrane;
[0012] The release film is removed.
[0013] In some embodiments, the release film is a high temperature resistant release film.
[0014] In some embodiments, the material of the substrate includes one or more of polyethylene terephthalate, polyethylene naphthalate, polyimide, and poly-4-methylpentene-1.
[0015] In some embodiments, the material of the release agent layer includes one or more of hydroxy polypropylene resin, polycarbonate, polyurethane resin, nitrocellulose, methyl phenyl silicone resin, polydimethylsiloxane and polytetrafluoroethylene.
[0016] In some embodiments, the first resin layer and the second resin layer each independently include a perfluorosulfonic acid resin.
[0017] In some embodiments, the step of preparing the first catalytic layer on one side of the release film comprises the following steps:
[0018] A first catalyst slurry is coated on one side surface of the release film, and the first catalytic layer is formed after drying; the first catalyst slurry includes a first catalyst, a first binder and a first dispersant, and the mass ratio of the first catalyst, the solute in the first binder and the first dispersant is 1:(0.15-1):(10-36).
[0019] In some embodiments, the first catalyst includes one or more of carbon-supported Pt and carbon-supported Pt alloy; further optionally, the content of Pt element in the first catalyst is 20wt%-70wt%.
[0020] In some embodiments, the first dispersant includes one or more of ethanol, methanol, isopropanol, n-propanol, n-butanol, ethylene glycol, and tert-butanol.
[0021] In some embodiments, the first binder includes perfluorosulfonic acid resin; optionally, the mass percentage of the perfluorosulfonic acid resin in the first binder is 5wt%-25wt%.
[0022] In some embodiments, the process conditions for coating the first catalyst slurry on one side of the release film include: a coating speed of 0.1 m / min-3 m / min, and a coating thickness of 30 μm-200 μm.
[0023] In some embodiments, the release film includes a substrate and a release agent layer disposed on at least one surface of the substrate.
[0024] In some embodiments, the step of preparing the first resin layer on one side surface of the ePTFE microporous membrane comprises the following steps:
[0025] A first perfluorosulfonic acid resin liquid is coated on one surface of the ePTFE microporous membrane, and the first resin layer is formed by drying.
[0026] In some embodiments, before the step of preparing the first resin layer on one surface of the ePTFE microporous membrane, the method further includes: providing a support membrane on a side of the ePTFE microporous membrane away from the first resin layer.
[0027] In some embodiments, after the step of laminating and pressing the first resin layer and the first catalyst layer, the method further includes: removing the support film.
[0028] In some embodiments, the material of the support membrane includes one or more of hydroxy polypropylene resin, polycarbonate, polyurethane resin, nitrocellulose, methylphenyl silicone resin, polydimethylsiloxane, polytetrafluoroethylene, polyethylene terephthalate, polyethylene naphthalate, polyimide and poly 4-methylpentene-1.
[0029] In some embodiments, the support film has a thickness of 25 μm-75 μm.
[0030] In some embodiments, the ePTFE microporous membrane has a thickness of 2 μm-15 μm, a pore size of 0.2 μm-10 μm, and a porosity of 50%-90%.
[0031] In some embodiments, in the first perfluorosulfonic acid resin solution, the mass fraction of the first perfluorosulfonic acid resin is 25%-50%.
[0032] In some embodiments, the coating thickness of the first perfluorosulfonic acid resin solution is 20 μm-50 μm.
[0033] In some embodiments, the process conditions of the drying treatment include: drying at 60° C.-80° C. for 0.3 h-1 h, and then drying at 80° C.-100° C. for 0.4 h-1.5 h.
[0034] In some embodiments, the pressing temperature is 120°C-170°C.
[0035] In some embodiments, the lamination line speed is 0.5 m / min-1 m / min.
[0036] In some embodiments, the step of preparing the second resin layer on the surface of the ePTFE microporous membrane away from the first resin layer comprises the following steps:
[0037] A second perfluorosulfonic acid resin liquid is coated on the surface of the ePTFE microporous membrane away from the first resin layer, and the second resin layer is formed after curing.
[0038] In some embodiments, the curing process conditions include: a curing temperature of 150° C.-180° C., and a curing time of 0.5 h-1.5 h.
[0039] In some embodiments, in the second perfluorosulfonic acid resin liquid, the mass fraction of the second perfluorosulfonic acid resin is 12%-18%.
[0040] In some embodiments, the coating thickness of the second perfluorosulfonic acid resin solution is 30 μm-70 μm.
[0041] In some embodiments, preparing the second catalytic layer on the surface of the second resin layer away from the ePTFE microporous membrane comprises the following steps:
[0042] A second catalyst slurry is coated on the surface of the second resin layer away from the ePTFE microporous membrane to form the second catalytic layer; the second catalyst slurry includes a second catalyst, a second binder and a second dispersant, and the mass ratio of the second catalyst, the solute in the second binder and the second dispersant is 1:(0.15-1):(10-36).
[0043] In some embodiments, the second catalyst includes one or more of carbon-supported Pt and carbon-supported Pt alloy; optionally, the content of Pt element in the second catalyst is 20wt%-70wt%.
[0044] In some embodiments, the second dispersant includes one or more of ethanol, methanol, isopropanol, n-propanol, n-butanol, ethylene glycol, and tert-butanol.
[0045] In some embodiments, the second binder includes perfluorosulfonic acid resin. Optionally, the mass percentage of the perfluorosulfonic acid resin in the second binder is 5wt%-25wt%.
[0046] In some embodiments, after the step of removing the release film, the method further comprises: soaking the intermediate obtained after removing the release film in an organic solvent, and drying the organic solvent to obtain a catalyst coating film.
[0047] In some embodiments, the organic solvent includes one or more of ethyl acetate, methyl acetate, toluene, and xylene.
[0048] In some embodiments, the infiltration time is 1 min-20 min.
[0049] The second aspect of the present application provides a catalyst coated membrane, which is prepared by the preparation method described in the first aspect of the present application.
[0050] The third aspect of the present application provides a membrane electrode, comprising at least one of the catalyst-coated membrane prepared by the preparation method described in the first aspect of the present application and the catalyst-coated membrane described in the second aspect of the present application.
[0051] A fourth aspect of the present application provides a fuel cell, comprising the membrane electrode described in the third aspect of the present application.
[0052] Compared with conventional technologies, the catalyst coated membrane and its preparation method, membrane electrode and application have at least the following advantages:
[0053] The release film in the above preparation method has certain tensile strength and deformation resistance, and can play a good supporting role for the first catalytic layer, the first resin layer, the ePTFE microporous membrane, the second resin layer and the second catalytic layer, solving the swelling and shrinkage problems of the proton exchange membrane in the traditional preparation method, and avoiding the poor structural uniformity and falling off problems of the first catalytic layer and the second catalytic layer; and the first catalytic layer is tightly bonded to the surface of the first resin layer, so that the surface flatness of the membrane electrode is high, the uniformity is good, and the electrochemical performance is excellent. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 This is a schematic diagram of the structure of L-CL according to one embodiment of the present application.
[0055] Figure 2 This is a schematic diagram of the PEM1 structure according to one embodiment of the present application.
[0056] Figure 3 A schematic diagram of coating of PEM1 according to one embodiment of the present application; Figure 3 The direction of the middle arrow is the advancing direction of the support membrane and the ePTFE microporous membrane.
[0057] Figure 4 Schematic diagram of the structure of L-CL-PEM1 according to one embodiment of the present application.
[0058] Figure 5 Schematic diagram of the structure of L-CL-PEM2 according to one embodiment of the present application.
[0059] Figure 6 Schematic diagram of the structure of L-CCM according to one embodiment of the present application.
[0060] Figure 7 This is a schematic diagram of the structure of a CCM according to one embodiment of the present application.
[0061] Figure 8 Schematic diagram of the structure of a release film according to one embodiment of the present application.
[0062] 1-release film; 11-release agent layer; 12-substrate; 2-first catalytic layer; 3-support membrane; 4-ePTFE microporous membrane; 5-first resin layer; 6-second resin layer; 7-second catalytic layer. DETAILED DESCRIPTION
[0063] In order to facilitate understanding of the present application, the present application will be described in more detail below. The preferred embodiments of the present application are provided in the specific embodiments. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0064] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The meaning of the term "multiple" in the present application is at least two, such as two, three, etc., unless otherwise clearly and specifically limited.
[0065] Those skilled in the art will appreciate that, in the methods of each embodiment or example, the order in which each step is written does not mean a strict order of execution and does not constitute any limitation on the implementation process, and the detailed order of execution of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or steps (a), (c) and (b), or steps (c), (a) and (b), etc.
[0066] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0067] An embodiment of the present application provides a method for preparing a catalyst coated membrane, wherein the catalyst coated membrane comprises a first catalyst layer, a first resin layer, an ePTFE microporous membrane, a second resin layer, and a second catalyst layer stacked in sequence; the method for preparing the catalyst coated membrane comprises the following steps:
[0068] Preparing a first catalytic layer on one side surface of the release film;
[0069] A first resin layer is prepared on the surface of an ePTFE microporous membrane (expanded polytetrafluoroethylene microporous membrane);
[0070] Laminating and pressing the first resin layer and the first catalyst layer;
[0071] Prepare a second resin layer on the surface of the ePTFE microporous membrane away from the first resin layer;
[0072] A second catalytic layer is prepared on the surface of the second resin layer away from the ePTFE microporous membrane;
[0073] Remove the release film.
[0074] Traditional technology uses two methods to coat the second side of the proton exchange membrane. One is to use an adsorption roller with porous paper to adsorb the proton exchange membrane coated with the first catalytic layer on the coating head back roller to alleviate the swelling phenomenon of the proton exchange membrane when it contacts the solvent when the second catalytic layer is coated; the other is to use an adhesive protective film to adhere to the proton exchange membrane coated with the first catalytic layer, and then coat the second catalytic layer. The first method cannot completely solve the swelling phenomenon of the proton membrane, and the proton membrane is prone to form fiber imprints on the surface of the porous paper or damage the catalytic layer; in the second method, the catalyst in the first catalytic layer is easily taken away when the protective film is peeled off.
[0075] In the above preparation method, the release film has a certain tensile strength and deformation resistance, and can play a good supporting role for the first catalytic layer, the first resin layer, the ePTFE microporous membrane, the second resin layer and the second catalytic layer, thereby solving the swelling and shrinkage problems of the proton exchange membrane in the traditional preparation method, and avoiding the poor structural uniformity and falling-off problems of the first catalytic layer and the second catalytic layer; due to the presence of the release film, the first catalytic layer and the second catalytic layer are deformed only in the thickness direction, and the force in the length and width directions is relatively uniform, and the first catalytic layer is tightly bonded to the surface of the first resin layer, so that the surface flatness of the membrane electrode is high, the uniformity is good, and the electrochemical performance is excellent; in addition, when the proton exchange membrane in the traditional preparation method is peeled off from the supporting release membrane, the uneven force will cause the proton exchange membrane to stretch and deform, while the above preparation method is supported by the release membrane during the entire catalyst coating membrane preparation process, thus avoiding the problems of uneven structure and falling-off of the second catalytic layer caused by swelling and stretching.
[0076] In some embodiments, the release film includes a substrate and a release agent layer disposed on at least one surface of the substrate. The release agent layer is provided with low viscosity, which is conducive to removing the release film from the first catalytic layer. Exemplarily, the release film can be torn off from the first catalytic layer to remove the release film.
[0077] In some embodiments, Figure 8 As shown, the release film 1 includes a substrate 12 and a release agent layer 11 disposed on at least one surface of the substrate 12. Optionally, the first catalytic layer 2 is disposed on the surface of the release agent layer 11.
[0078] In some embodiments, the release film is a high temperature resistant release film, so that at a relatively high temperature, the release film can still provide good support for the first catalyst layer, the first resin layer, the ePTFE microporous membrane, the second resin layer and the second catalyst layer.
[0079] In some embodiments, the material of the substrate includes one or more of polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyimide (PI) and poly-4-methylpentene-1 (TPX). The material of the substrate is selected from the above materials, which can further enhance the support effect of the release film on the first catalyst layer, the first resin layer, the ePTFE microporous membrane, the second resin layer and the second catalyst layer, thereby further enhancing the electrochemical performance of the membrane electrode.
[0080] In some embodiments, the material of the release agent layer includes one or more of hydroxy polypropylene resin, polycarbonate, polyurethane resin, nitrocellulose, methylphenyl silicone resin, polydimethylsiloxane and polytetrafluoroethylene. This is conducive to removing the release film from the first catalyst layer, reducing or avoiding the material of the release agent layer remaining on the surface of the first catalyst layer, thereby further improving the electrochemical performance of the membrane electrode.
[0081] In some embodiments, the first resin layer and the second resin layer each independently comprise a perfluorosulfonic acid resin. The perfluorosulfonic acid resin is used to conduct protons.
[0082] In some embodiments, preparing the first catalytic layer on one side surface of the release film comprises the following steps:
[0083] A first catalyst slurry is coated on one side of the release film to form a first catalytic layer after drying; the first catalyst slurry includes a first catalyst, a first binder and a first dispersant, and the mass ratio of the first catalyst, the solute in the first binder and the first dispersant is 1:(0.15-1):(10-36).
[0084] In the above embodiment, controlling the mass ratio of the first catalyst, the solute in the first binder and the first dispersant to be within the above range is beneficial to improving the electrochemical performance of the membrane electrode. It is understood that the mass ratio of the first catalyst, the solute in the first binder and the first dispersant includes but is not limited to: 1:0.15:10, 1:0.2:13, 1:0.3:15, 1:0.4:19.5, 1:0.5:23.5, 1:0.6:25, 1:0.64:25.7, 1:0.7:28, 1:0.9:32, 1:1:36.
[0085] In some embodiments, the first catalyst includes one or more of carbon-supported Pt and carbon-supported Pt alloy; further optionally, the content of Pt element in the first catalyst is 20wt%-70wt%. It is understood that the content of Pt element in the first catalyst includes but is not limited to: 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%.
[0086] In some embodiments, the first dispersant includes one or more of ethanol, methanol, isopropanol, n-propanol, n-butanol, ethylene glycol, and tert-butanol.
[0087] In some embodiments, the first binder includes a perfluorosulfonic acid resin; optionally, the mass percentage of the perfluorosulfonic acid resin in the first binder is 5wt%-25wt%. It is understood that the perfluorosulfonic acid resin is a solute in the first binder. It is understood that the mass percentage of the perfluorosulfonic acid resin in the first binder includes but is not limited to: 5wt%, 10wt%, 15wt%, 20wt%, 25wt%.
[0088] In some embodiments, the process conditions for coating the first catalyst slurry on one side of the release film include: a coating speed of 0.1 m / min-3 m / min, and a coating thickness of 30 μm-200 μm.
[0089] In some embodiments, preparing a first resin layer on one side surface of the ePTFE microporous membrane comprises the following steps:
[0090] A first perfluorosulfonic acid resin solution is applied to one surface of the ePTFE microporous membrane and dried to form a first resin layer.
[0091] In some embodiments, before the step of preparing the first resin layer on one side of the ePTFE microporous membrane, the step further includes: arranging a support membrane on the side of the ePTFE microporous membrane away from the first resin layer. The support membrane can support the ePTFE microporous membrane, avoid deformation of the interface between the ePTFE microporous membrane and the support membrane, and further improve the electrochemical performance of the membrane electrode.
[0092] In some embodiments, after the step of laminating and pressing the first resin layer and the first catalytic layer, the method further includes: removing the support film. The support film is arranged on the side of the ePTFE microporous membrane away from the first resin layer, for example, the support film can be fixed by an adsorption roller, and then the ePTFE microporous membrane is placed on the support film, and when the first resin layer is prepared on the surface of the ePTFE microporous membrane away from the support film, the resin in the first resin layer penetrates the ePTFE microporous membrane, thereby fixing the ePTFE microporous membrane to the support film; or after the ePTFE microporous membrane and the support film are laminated, the support film and the ePTFE microporous membrane can be fixed by the tension of a roll-to-roll device.
[0093] In some embodiments, the material of the support film includes one or more of hydroxy polypropylene resin, polycarbonate, polyurethane resin, nitrocellulose, methyl phenyl silicone resin, polydimethylsiloxane, polytetrafluoroethylene, polyethylene terephthalate, polyethylene naphthalate, polyimide and poly 4-methylpentene-1. The material of the support film can be any one of hydroxy polypropylene resin, polycarbonate, polyurethane resin, nitrocellulose, methyl phenyl silicone resin, polydimethylsiloxane, polytetrafluoroethylene, polyethylene terephthalate, polyethylene naphthalate, polyimide and poly 4-methylpentene-1, or a composite material thereof, which can be, for example, a composite material of at least one of hydroxy polypropylene resin, polycarbonate, polyurethane resin, nitrocellulose, methyl phenyl silicone resin, polydimethylsiloxane and polytetrafluoroethylene and at least one of polyethylene terephthalate, polyethylene naphthalate, polyimide and poly 4-methylpentene-1.
[0094] In some embodiments, the thickness of the support membrane is 25 μm-75 μm. The thickness of the support membrane includes but is not limited to: 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm.
[0095] In some embodiments, the method for preparing a catalyst coated membrane comprises the following steps:
[0096] A first catalytic layer 2 is prepared on one side of the release film 1, and the obtained product is recorded as L-CL (eg Figure 1 shown);
[0097] A support membrane 3 is provided on one side surface of the ePTFE microporous membrane 4, and a first resin layer 5 is prepared on the surface of the ePTFE microporous membrane 4 away from the support membrane 3. The obtained product is recorded as PEM1 (eg Figure 2 and Figure 3 shown);
[0098] After the first resin layer 5 and the first catalyst layer 2 are laminated (that is, the first resin layer 5 and the first catalyst layer 2 are pressed together), the support film 3 is removed, and the obtained product is recorded as L-CL-PEM1 (such as Figure 4 shown);
[0099] The second resin layer 6 is prepared on the surface of the ePTFE microporous membrane 4 away from the first resin layer 5, and the obtained product is recorded as L-CL-PEM2 (such as Figure 5 shown);
[0100] The second catalytic layer 7 is prepared on the surface of the second resin layer 6 away from the ePTFE microporous membrane 4, and the obtained product is recorded as L-CL-PEM2-CL, abbreviated as L-CCM (such as Figure 6 shown);
[0101] Remove the release film 1.
[0102] In the above embodiment, the obtained catalyst coated membrane CCM is as follows Figure 7 As shown, the catalyst coated membrane includes a first catalyst layer 2, a first resin layer 5, an ePTFE microporous membrane 4, a second resin layer 6 and a second catalyst layer 7 which are stacked in sequence. Optionally, after the step of removing the release film 1, the step of soaking the intermediate obtained after removing the release film 1 in an organic solvent and drying it to obtain a catalyst coated membrane is also included. Thus, the release film remaining on the first catalyst layer 1 can be removed, thereby further improving the electrochemical performance of the membrane electrode. Optionally, it includes one or more of ethyl acetate, methyl acetate, toluene and xylene; Optionally, the soaking time is 1min-20min.
[0103] In some embodiments, the ePTFE microporous membrane has a thickness of 2 μm-15 μm, a pore size of 0.2 μm-10 μm, and a porosity of 50%-90%.
[0104] In some embodiments, in the first perfluorosulfonic acid resin solution, the mass fraction of the first perfluorosulfonic acid resin is 25%-50%.
[0105] In some embodiments, the coating thickness of the first perfluorosulfonic acid resin solution is 20 μm-50 μm.
[0106] In some embodiments, the process conditions of the drying treatment include: drying at 60°C-80°C for 0.3h-1h, and then drying at 80°C-100°C for 0.4h-1.5h. In this way, it is possible to avoid the formation of bubbles in the first perfluorosulfonic acid resin liquid due to high temperature and fast volatilization of the organic solvent during the initial drying, and the bubbles are easily fixed in the first resin layer during the drying process of the first perfluorosulfonic acid resin, thereby increasing the compactness of the proton exchange membrane. After the organic solvent is completely volatilized, high-temperature drying helps to eliminate stress and completely dry the first perfluorosulfonic acid resin.
[0107] In some embodiments, the pressing temperature is 120° C.-170° C. Controlling the pressing temperature within the above range is conducive to further improving the bonding force between the first resin layer and the first catalyst layer. The pressing temperature includes but is not limited to: 120° C., 130° C., 140° C., 150° C., 160° C., 170° C.
[0108] In some embodiments, the lamination line speed is 0.5 m / min-1 m / min. Controlling the lamination temperature within the above range is conducive to further improving the bonding force between the first resin layer and the first catalyst layer. The lamination line speed includes but is not limited to: 0.5 m / min, 0.6 m / min, 0.7 m / min, 0.8 m / min, 0.9 m / min, 1 m / min.
[0109] In some embodiments, preparing the second resin layer on the surface of the ePTFE microporous membrane away from the first resin layer comprises the following steps:
[0110] A second perfluorosulfonic acid resin liquid is coated on the surface of the ePTFE microporous membrane away from the first resin layer, and the second resin layer is formed after curing.
[0111] In some embodiments, the curing process conditions include: a curing temperature of 150°C-180°C, and a curing time of 0.5h-1.5h. Controlling the curing temperature and curing time within the above range is conducive to the thorough drying of the second resin layer, enhancing the bonding between the fibers in the ePTFE microporous membrane and the second perfluorosulfonic acid resin, structural shaping of the fibers in the ePTFE microporous membrane and the second perfluorosulfonic acid resin at high temperatures and stress elimination during the cooling process, and testing the volatilization effect of the solvent (if there is a volatile organic solvent remaining in the second perfluorosulfonic acid resin, it will cause yellowing at high temperatures).
[0112] In some embodiments, in the second perfluorosulfonic acid resin solution, the mass fraction of the second perfluorosulfonic acid resin is 12%-18%. It is understood that the mass fraction of the second perfluorosulfonic acid resin includes but is not limited to: 12%, 13%, 14%, 15%, 16%, 17%, 18%.
[0113] In some embodiments, the coating thickness of the second perfluorosulfonic acid resin solution is 30 μm-70 μm. It is understood that the coating thickness of the second perfluorosulfonic acid resin solution includes but is not limited to: 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm.
[0114] In some embodiments, preparing the second catalytic layer on the surface of the second resin layer away from the ePTFE microporous membrane comprises the following steps:
[0115] A second catalyst slurry is applied on the surface of the second resin layer away from the ePTFE microporous membrane to form a second catalytic layer; the second catalyst slurry includes a second catalyst, a second binder, and a second dispersant, and the mass ratio of the solute in the second catalyst, the second binder, and the second dispersant is 1: (0.15-1): (10-36). Controlling the mass ratio of the solute in the second catalyst, the second binder, and the second dispersant to the above range is beneficial to improving the electrochemical performance of the membrane electrode. It is understood that the mass ratio of the solute in the second catalyst, the second binder, and the second dispersant includes but is not limited to: 1: 0.15: 10, 1: 0.2: 13, 1: 0.3: 15, 1: 0.4: 19.5, 1: 0.5: 23.5, 1: 0.6: 25, 1: 0.64: 25.7, 1: 0.7: 28, 1: 0.9: 32, 1: 1: 36.
[0116] In some embodiments, the second catalyst includes one or more of carbon-supported Pt and carbon-supported Pt alloy. Optionally, the content of Pt element in the second catalyst is 20wt%-70wt%. It is understood that the content of Pt element in the second catalyst includes but is not limited to: 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%.
[0117] In some embodiments, the second dispersant includes one or more of ethanol, methanol, isopropanol, n-propanol, n-butanol, ethylene glycol, and tert-butanol.
[0118] In some embodiments, the second binder includes a perfluorosulfonic acid resin. Optionally, the mass percentage of the perfluorosulfonic acid resin in the second binder is 5wt%-25wt%. It is understood that the perfluorosulfonic acid resin is a solute in the second binder. It is understood that the mass percentage of the perfluorosulfonic acid resin in the second binder includes but is not limited to: 5wt%, 10wt%, 15wt%, 20wt%, 25wt%.
[0119] In some embodiments, removing the release film comprises the following step: tearing off the release film. For example, the release film may be torn off using external force to remove the release film.
[0120] In some embodiments, after the step of removing the release film, the step further includes: soaking the intermediate obtained after removing the release film in an organic solvent, drying, and obtaining a catalyst coating film. In this way, the release film remaining on the first catalytic layer can be removed, thereby further improving the electrochemical performance of the membrane electrode. Optionally, the organic solvent includes one or more of ethyl acetate, methyl acetate, toluene and xylene; optionally, the soaking time is 1 min-20 min.
[0121] Another embodiment of the present application provides a catalyst coated membrane, which is prepared by the above-mentioned preparation method.
[0122] For reference Figure 7 The catalyst coated membrane includes a first catalytic layer 2, a first resin layer 5, an ePTFE microporous membrane 4, a second resin layer 6 and a second catalytic layer 7 which are stacked in sequence.
[0123] Yet another embodiment of the present application provides a membrane electrode, comprising a catalyst coated membrane obtained by the above preparation method and at least one of the above catalyst coated membranes.
[0124] Exemplarily, the membrane electrode may include a catalyst coated membrane and a gas diffusion layer, wherein the gas diffusion layer is arranged on both sides of the catalyst coated membrane, and the catalyst coated membrane is a catalyst coated membrane prepared by the preparation method described above in the present application and at least one of the catalyst coated membranes described above in the present application.
[0125] Another embodiment of the present application provides a fuel cell, comprising the above-mentioned membrane electrode.
[0126] Another embodiment of the present application further provides an electrical device, comprising the above-mentioned fuel cell. The above-mentioned fuel cell can be used as a power source or energy storage unit in the above-mentioned electrical device, such as an electric vehicle, a mobile phone, a laptop computer or a household appliance.
[0127] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If the techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be obtained commercially.
[0128] Example 1
[0129] Prepare CCM as follows:
[0130] (1) Preparation of the first catalytic layer
[0131] A first catalyst slurry is coated on one side of the TPX release film, and a first catalyst layer is formed after drying. The obtained product is recorded as L-CL; wherein the mass ratio of solid catalyst particles, binder (solute) and dispersant in the first catalyst slurry is 1:0.64:25.7; the solid catalyst particles are carbon-supported Pt, and the metal Pt content is 20wt%; the dispersant is isopropanol; and the binder is 20wt% perfluorosulfonic acid resin liquid;
[0132] (2) Preparation of the first resin layer
[0133] A support membrane is provided on one side of the ePTFE microporous membrane to support the ePTFE microporous membrane and prevent the ePTFE microporous membrane from being deformed in its length and width directions, and then a first perfluorosulfonic acid resin liquid is coated on the surface of the ePTFE microporous membrane away from the support membrane, and dried at 60°C for 0.5h and then at 100°C for 0.6h to form a first resin layer. The obtained product is recorded as PEM1; wherein the mass fraction of the first perfluorosulfonic acid resin liquid is 28%, the gap between the coating head and the ePTFE microporous membrane is set to 30μm, the material of the support membrane is a composite material of polydimethylsiloxane and polyimide, the thickness of the support membrane is 50μm, the thickness of the ePTFE microporous membrane is 8μm, the pore size is 0.3μm, and the porosity is 70%;
[0134] (3) After the first resin layer and the first catalyst layer are laminated, hot pressing is performed and the support film is removed
[0135] The side of the first resin layer of L-CL pasted to PEM1 is passed through a heated laminating roller. The gap between the laminating rollers is controlled at 15 μm after subtracting the thickness of the support films of L-CL and PEM1. The laminating temperature is set at 140°C and the line speed is controlled at 0.6 m / min. The support film on PEM1 is torn off, and the obtained product is recorded as L-CL-PEM1.
[0136] (4) Preparation of the Second Resin Layer
[0137] The surface of L-CL-PEM1 (the surface of the ePTFE microporous membrane away from the first resin layer) was coated with a second perfluorosulfonic acid resin liquid, the mass fraction of the second perfluorosulfonic acid resin liquid was 16%, the gap between the coating head and the ePTFE microporous membrane was set to 35 μm, and dried at 100°C for 0.8h to form L-CL-PEM2, which was passed through a drying tunnel, and the curing temperature was set to 160°C for 1h;
[0138] (5) Preparation of the second catalytic layer
[0139] The second catalyst slurry is coated on the surface of L-CL-PEM2 (the surface of the second resin layer away from the ePTFE microporous membrane) to form a second catalytic layer. The obtained product is recorded as L-CL-PEM2-CL, abbreviated as L-CCM; the mass ratio of solid catalyst particles, binder (solute) and dispersant in the second catalyst slurry is 1:0.6:25, the solid catalyst particles are carbon-supported Pt, the metal Pt content is 50wt%, the dispersant is isopropanol, and the binder is 20wt% perfluorosulfonic acid resin liquid; the TPX release film is torn off to obtain CCM, wherein the total thickness of the first resin layer, the ePTFE microporous membrane and the second resin layer is 15μm.
[0140] Example 2
[0141] Prepare CCM as follows:
[0142] (1) Preparation of the first catalytic layer
[0143] A first catalyst slurry is coated on one side of the TPX release film, and a first catalyst layer is formed after drying. The obtained product is recorded as L-CL; wherein the mass ratio of solid catalyst particles, binder (solute) and dispersant in the first catalyst slurry is 1:0.72:27; the solid catalyst particles are carbon-supported Pt, and the metal Pt content is 20wt%; the dispersant is isopropanol; and the binder is 20wt% perfluorosulfonic acid resin liquid;
[0144] (2) Preparation of the first resin layer
[0145] A support membrane is provided on one side of the ePTFE microporous membrane to support the ePTFE microporous membrane and prevent the ePTFE microporous membrane from being deformed in its length and width directions, and then a first perfluorosulfonic acid resin liquid is coated on the surface of the ePTFE microporous membrane away from the support membrane, and dried at 60°C for 0.5h and then at 100°C for 0.6h to form a first resin layer. The obtained product is recorded as PEM1; wherein the mass fraction of the first perfluorosulfonic acid resin liquid is 28%, the gap between the coating head and the ePTFE microporous membrane is set to 30μm, the material of the support membrane is a composite material of polydimethylsiloxane and polyimide, the thickness of the support membrane is 50μm, the thickness of the ePTFE microporous membrane is 8μm, the pore size is 0.3μm, and the porosity is 70%;
[0146] (3) After the first resin layer and the first catalyst layer are laminated, hot pressing is performed and the support film is removed
[0147] The side of the first resin layer of L-CL pasted to PEM1 is passed through a heated laminating roller. The gap between the laminating rollers is controlled at 15 μm after subtracting the thickness of the support films of L-CL and PEM1. The laminating temperature is set at 140°C and the line speed is controlled at 0.6 m / min. The support film on PEM1 is torn off, and the obtained product is recorded as L-CL-PEM1.
[0148] (4) Preparation of the Second Resin Layer
[0149] The surface of L-CL-PEM1 (the surface of the ePTFE microporous membrane away from the first resin layer) was coated with a second perfluorosulfonic acid resin liquid, the mass fraction of the second perfluorosulfonic acid resin liquid was 16%, the gap between the coating head and the ePTFE microporous membrane was set to 35 μm, and dried at 100°C for 0.8h to form L-CL-PEM2, which was passed through a drying tunnel at a temperature set to 160°C for 1h;
[0150] (5) Preparation of the second catalytic layer
[0151] A second catalyst slurry is coated on the surface of L-CL-PEM2 (the surface of the second resin layer away from the ePTFE microporous membrane) to form a second catalytic layer. The obtained product is recorded as L-CL-PEM2-CL, abbreviated as L-CCM; the mass ratio of solid catalyst particles, binder (solute) and dispersant in the second catalyst slurry is 1:0.5:23.5, the solid catalyst particles are carbon-supported Pt, the metal Pt content is 50wt%, the dispersant is isopropanol, and the binder is 20wt% perfluorosulfonic acid resin liquid; the TPX release film is torn off to obtain CCM, wherein the total thickness of the first resin layer, the ePTFE microporous membrane and the second resin layer is 15μm.
[0152] Example 3
[0153] Prepare CCM as follows:
[0154] (1) Preparation of the first catalytic layer
[0155] A first catalyst slurry is coated on one side of the TPX release film, and a first catalyst layer is formed after drying. The obtained product is recorded as L-CL; wherein the mass ratio of solid catalyst particles, binder (solute) and dispersant in the first catalyst slurry is 1:0.64:25.7; the solid catalyst particles are carbon-supported Pt, and the metal Pt content is 20wt%; the dispersant is isopropanol; and the binder is 20wt% perfluorosulfonic acid resin liquid;
[0156] (2) Preparation of the first resin layer
[0157] A support membrane is provided on one side of the ePTFE microporous membrane to support the ePTFE microporous membrane and prevent the ePTFE microporous membrane from being deformed in its length and width directions, and then a first perfluorosulfonic acid resin liquid is coated on the surface of the ePTFE microporous membrane away from the support membrane, and dried at 60°C for 0.6h and then at 100°C for 0.8h to form a first resin layer. The obtained product is recorded as PEM1; wherein the mass fraction of the first perfluorosulfonic acid resin liquid is 20%, the gap between the coating head and the ePTFE microporous membrane is set to 40μm, the material of the support membrane is a composite material of polydimethylsiloxane and polyimide, the thickness of the support membrane is 50μm, the thickness of the ePTFE microporous membrane is 8μm, the pore size is 0.3μm, and the porosity is 70%;
[0158] (3) After the first resin layer and the first catalyst layer are laminated, hot pressing is performed and the support film is removed
[0159] The resin side of L-CL was pasted to PEM1 and passed through a heated lamination roller. The gap between the lamination rollers was controlled at 15 μm after subtracting the thickness of the support films of L-CL and PEM1. The lamination temperature was set at 150°C and the line speed was controlled at 0.5 m / min. The support film on PEM1 was torn off and the obtained product was recorded as L-CL-PEM1.
[0160] (4) Preparation of the Second Resin Layer
[0161] The surface of L-CL-PEM1 (the surface of the ePTFE microporous membrane away from the first resin layer) was coated with a second perfluorosulfonic acid resin liquid, the mass fraction of the second perfluorosulfonic acid resin liquid was 16%, the gap between the coating head and the ePTFE microporous membrane was set to 35 μm, and dried at 100°C for 0.8h to form L-CL-PEM2, which was passed through a drying tunnel, and the curing temperature was set to 160°C for 1h;
[0162] (5) Preparation of the second catalytic layer
[0163] The second catalyst slurry is coated on the surface of L-CL-PEM2 (the surface of the second resin layer away from the ePTFE microporous membrane) to form a second catalytic layer. The obtained product is recorded as L-CL-PEM2-CL, abbreviated as L-CCM; the mass ratio of solid catalyst particles, binder (solute) and dispersant in the second catalyst slurry is 1:0.6:25, the solid catalyst particles are carbon-supported Pt, the metal Pt content is 50wt%, the dispersant is isopropanol, and the binder is 20wt% perfluorosulfonic acid resin liquid; the TPX release film is torn off to obtain CCM, wherein the total thickness of the first resin layer, the ePTFE microporous membrane and the second resin layer is 15μm.
[0164] Example 4
[0165] Prepare CCM as follows:
[0166] (1) Preparation of the first catalytic layer
[0167] A first catalyst slurry is coated on one side of the TPX release film, and a first catalyst layer is formed after drying. The obtained product is recorded as L-CL; wherein the mass ratio of solid catalyst particles, binder (solute) and dispersant in the first catalyst slurry is 1:0.72:27; the solid catalyst particles are carbon-supported Pt, and the metal Pt content is 20wt%; the dispersant is isopropanol; and the binder is 20wt% perfluorosulfonic acid resin liquid;
[0168] (2) Preparation of the first resin layer
[0169] A support membrane is provided on one side of the ePTFE microporous membrane to support the ePTFE microporous membrane and prevent the ePTFE microporous membrane from being deformed in its length and width directions, and then a first perfluorosulfonic acid resin liquid is coated on the surface of the ePTFE microporous membrane away from the support membrane, and dried at 60°C for 0.6h and then at 100°C for 0.8h to form a first resin layer. The obtained product is recorded as PEM1; wherein the mass fraction of the first perfluorosulfonic acid resin liquid is 20%, the gap between the coating head and the ePTFE microporous membrane is set to 40μm, the material of the support membrane is a composite material of polydimethylsiloxane and polyimide, the thickness of the support membrane is 50μm, the thickness of the ePTFE microporous membrane is 8μm, the pore size is 0.3μm, and the porosity is 70%;
[0170] (3) After the first resin layer and the first catalyst layer are laminated, hot pressing is performed and the support film is removed
[0171] The side of the first resin layer of L-CL pasted to PEM1 is passed through a heated lamination roller. The gap between the lamination rollers is controlled at 15 μm after subtracting the thickness of the support films of L-CL and PEM1. The lamination temperature is set at 150°C and the line speed is controlled at 0.5 m / min. The support film on PEM1 is torn off, and the obtained product is recorded as L-CL-PEM1.
[0172] (4) Preparation of the Second Resin Layer
[0173] The surface of L-CL-PEM1 (the surface of the ePTFE microporous membrane away from the first resin layer) was coated with a second perfluorosulfonic acid resin liquid, the mass fraction of the second perfluorosulfonic acid resin liquid was 16%, the gap between the coating head and the ePTFE microporous membrane was set to 35 μm, and dried at 100°C for 0.8h to form L-CL-PEM2, which was passed through a drying tunnel, and the curing temperature was set to 160°C for 1h;
[0174] (5) Preparation of the second catalytic layer
[0175] A second catalyst slurry is coated on the surface of L-CL-PEM2 (the surface of the second resin layer away from the ePTFE microporous membrane) to form a second catalytic layer. The obtained product is recorded as L-CL-PEM2-CL, abbreviated as L-CCM; the mass ratio of solid catalyst particles, binder (solute) and dispersant in the second catalyst slurry is 1:0.5:23.5, the solid catalyst particles are carbon-supported Pt, the metal Pt content is 50wt%, the dispersant is isopropanol, and the binder is 20wt% perfluorosulfonic acid resin liquid; the TPX release film is torn off to obtain CCM, wherein the total thickness of the first resin layer, the ePTFE microporous membrane and the second resin layer is 15μm.
[0176] Example 5
[0177] Prepare CCM as follows:
[0178] (1) Preparation of the first catalytic layer
[0179] A first catalyst slurry is coated on one side of the TPX release film, and a first catalyst layer is formed after drying. The obtained product is recorded as L-CL; wherein the mass ratio of solid catalyst particles, binder (solute) and dispersant in the first catalyst slurry is 1:0.64:25.7; the solid catalyst particles are carbon-supported Pt, and the metal Pt content is 20wt%; the dispersant is isopropanol; and the binder is 20wt% perfluorosulfonic acid resin liquid;
[0180] (2) Preparation of the first resin layer
[0181] A support membrane is provided on one side of the ePTFE microporous membrane to support the ePTFE microporous membrane and prevent the ePTFE microporous membrane from being deformed in its length and width directions, and then a first perfluorosulfonic acid resin liquid is coated on the surface of the ePTFE microporous membrane away from the support membrane, and dried at 60°C-80°C for 0.6h and then at 100°C for 0.8h to form a first resin layer, and the obtained product is recorded as PEM1; wherein the mass fraction of the first perfluorosulfonic acid resin liquid is 20%, the gap between the coating head and the ePTFE microporous membrane is set to 40μm, the material of the support membrane is a composite material of polydimethylsiloxane and polyimide, the thickness of the support membrane is 50μm, the thickness of the ePTFE microporous membrane is 8μm, the pore size is 0.3μm, and the porosity is 70%;
[0182] (3) After the first resin layer and the first catalyst layer are laminated, hot pressing is performed and the support film is removed
[0183] The side of the first resin layer of L-CL pasted to PEM1 is passed through a heated lamination roller. The gap between the lamination rollers is controlled at 15 μm after subtracting the thickness of the support films of L-CL and PEM1. The lamination temperature is set at 150°C and the line speed is controlled at 0.5 m / min. The support film on PEM1 is torn off, and the obtained product is recorded as L-CL-PEM1.
[0184] (4) Preparation of the Second Resin Layer
[0185] A second perfluorosulfonic acid resin liquid was coated on the surface of L-CL-PEM1 (the surface of the ePTFE microporous membrane away from the first resin layer), the mass fraction of the second perfluorosulfonic acid resin liquid was 16%, the gap between the coating head and the ePTFE microporous membrane was set to 35 μm, and dried at 100°C for 0.8h to form L-CL-PEM2, and passed through a drying tunnel, the curing temperature was set to 180°C, and the curing time was 0.65h;
[0186] (5) Preparation of the second catalytic layer
[0187] The second catalyst slurry is coated on the surface of L-CL-PEM2 (the surface of the second resin layer away from the ePTFE microporous membrane) to form a second catalytic layer. The obtained product is recorded as L-CL-PEM2-CL, abbreviated as L-CCM; the mass ratio of solid catalyst particles, binder (solute) and dispersant in the second catalyst slurry is 1:0.6:25, the solid catalyst particles are carbon-supported Pt, the metal Pt content is 50wt%, the dispersant is isopropanol, and the binder is 20wt% perfluorosulfonic acid resin liquid; the TPX release film is torn off to obtain CCM, wherein the total thickness of the first resin layer, the ePTFE microporous membrane and the second resin layer is 15μm.
[0188] Example 6
[0189] Prepare CCM as follows:
[0190] (1) Preparation of the first catalytic layer
[0191] A first catalyst slurry is coated on one side of the TPX release film, and a first catalyst layer is formed after drying. The obtained product is recorded as L-CL; wherein the mass ratio of solid catalyst particles, binder (solute) and dispersant in the first catalyst slurry is 1:0.72:27; the solid catalyst particles are carbon-supported Pt, and the metal Pt content is 20wt%; the dispersant is isopropanol; and the binder is 20wt% perfluorosulfonic acid resin liquid;
[0192] (2) Preparation of the first resin layer
[0193] A support membrane is provided on one side of the ePTFE microporous membrane to support the ePTFE microporous membrane and prevent the ePTFE microporous membrane from being deformed in its length and width directions, and then a first perfluorosulfonic acid resin liquid is coated on the surface of the ePTFE microporous membrane away from the support membrane, and dried at 60°C for 0.6h and then at 100°C for 0.8h to form a first resin layer, and the obtained product is recorded as PEM1; wherein the mass fraction of the first perfluorosulfonic acid resin liquid is 20%, and the gap between the coating head and the ePTFE microporous membrane is set to 40μm; the material of the support membrane is a composite material of polydimethylsiloxane and polyimide, the thickness of the support membrane is 50μm, the thickness of the ePTFE microporous membrane is 8μm, the pore size is 0.3μm, and the porosity is 70%;
[0194] (3) After the first resin layer and the first catalyst layer are laminated, hot pressing is performed and the support film is removed
[0195] The side of the first resin layer of L-CL pasted to PEM1 is passed through a heated lamination roller. The gap between the lamination rollers is controlled at 15 μm after subtracting the thickness of the support films of L-CL and PEM1. The lamination temperature is set at 150°C and the line speed is controlled at 0.5 m / min. The support film on PEM1 is torn off, and the obtained product is recorded as L-CL-PEM1.
[0196] (4) Preparation of the Second Resin Layer
[0197] A second perfluorosulfonic acid resin liquid was coated on the surface of L-CL-PEM1 (the surface of the ePTFE microporous membrane away from the first resin layer), the mass fraction of the second perfluorosulfonic acid resin liquid was 16%, the gap between the coating head and the ePTFE microporous membrane was set to 35 μm, and dried at 100° C. for 0.8 h to form L-CL-PEM2, which was passed through a drying tunnel at a temperature set to 180° C. for 0.65 h;
[0198] (5) Preparation of the second catalytic layer
[0199] A second catalyst slurry is coated on the surface of L-CL-PEM2 (the surface of the second resin layer away from the ePTFE microporous membrane) to form a second catalytic layer. The obtained product is recorded as L-CL-PEM2-CL, abbreviated as L-CCM; the mass ratio of solid catalyst particles, binder (solute) and dispersant in the second catalyst slurry is 1:0.5:23.5, the solid catalyst particles are carbon-supported Pt, the metal Pt content is 50wt%, the dispersant is isopropanol, and the binder is 20wt% perfluorosulfonic acid resin liquid; the TPX release film is torn off to obtain CCM, wherein the total thickness of the first resin layer, the ePTFE microporous membrane and the second resin layer is 15μm.
[0200] Example 7
[0201] The preparation method of CCM is basically the same as that of Example 1, except that: in the first catalyst slurry in step (1), the mass ratio of solid catalyst particles, binder (solute) and dispersant is 1:0.15:10, the solid catalyst particles are carbon-supported Pt, and the metal Pt content is 20wt%; the dispersant is isopropanol; the binder is 20wt% perfluorosulfonic acid resin liquid; in the second catalyst slurry in step (2), the mass ratio of solid catalyst particles, binder (solute) and dispersant is 1:0.6:25, the solid catalyst particles are carbon-supported Pt, the metal Pt content is 50wt%, the dispersant is isopropanol, and the binder is 20wt% perfluorosulfonic acid resin liquid.
[0202] Example 8
[0203] The preparation method of CCM is basically the same as that of Example 1, except that: in the first catalyst slurry in step (1), the mass ratio of solid catalyst particles, binder (solute) and dispersant is 1:1:36, the solid catalyst particles are carbon-supported Pt, and the metal Pt content is 20wt%; the dispersant is isopropanol; the binder is 20wt% perfluorosulfonic acid resin liquid; in the second catalyst slurry in step (2), the mass ratio of solid catalyst particles, binder (solute) and dispersant is 1:0.6:25, the solid catalyst particles are carbon-supported Pt, the metal Pt content is 50wt%, the dispersant is isopropanol, and the binder is 20wt% perfluorosulfonic acid resin liquid.
[0204] Example 9
[0205] The preparation method of CCM is basically the same as that of Example 1, except that: in this example, the CCM obtained in step (5) is soaked in ethyl acetate for 1 minute, taken out and dried.
[0206] Comparative Example 1
[0207] Prepare CCM as follows:
[0208] (1) Preparation of the first catalytic layer
[0209] A first catalyst slurry is coated on one side of the TPX release film, and a first catalyst layer is formed after drying. The obtained product is recorded as L-CL; wherein the mass ratio of solid catalyst particles, binder (solute) and dispersant in the first catalyst slurry is 1:0.64:25.7; the solid catalyst particles are carbon-supported Pt, and the metal Pt content is 20wt%; the dispersant is isopropanol; and the binder is 20wt% perfluorosulfonic acid resin liquid;
[0210] (2) Preparation of L-CL-PEM
[0211] L-CL was attached to a 15 μm proton exchange membrane (manufacturer: Gore, USA, model: M850.15) and passed through a heated lamination roller. The value of the lamination roller gap was controlled at 15 μm after deducting the total thickness of L-CL and the thickness of the support membrane of PEM1 (composite membrane of polydimethylsiloxane and polyimide). The hot pressing temperature was set at 150°C and the line speed was controlled at 0.5 m / min to obtain L-CL-PEM.
[0212] (3) Preparation of the second catalytic layer
[0213] A second catalyst slurry is coated on the surface of L-CL-PEM to form a second catalytic layer. The obtained product is recorded as L-CL-PEM-CL, abbreviated as L-CCM; the mass ratio of solid catalyst particles, binder (solute) and dispersant in the second catalyst slurry is 1:0.6:25, the solid catalyst particles are carbon-supported Pt, the metal Pt content is 50wt%, the dispersant is isopropanol, and the binder is 20wt% perfluorosulfonic acid resin liquid; the TPX release film is torn off to obtain CCM.
[0214] Comparative Example 2
[0215] Prepare CCM as follows:
[0216] (1) Preparation of the first catalytic layer
[0217] A first catalyst slurry is coated on one side of the TPX release film, and a first catalyst layer is formed after drying. The obtained product is recorded as L-CL; wherein the mass ratio of solid catalyst particles, binder (solute) and dispersant in the first catalyst slurry is 1:0.72:27; the solid catalyst particles are carbon-supported Pt, and the metal Pt content is 20wt%; the dispersant is isopropanol; and the binder is 20wt% perfluorosulfonic acid resin liquid;
[0218] (2) Preparation of L-CL-PEM
[0219] L-CL was pasted with a 15μm proton exchange membrane (manufacturer: Dongyue Future Hydrogen Energy, model: DM2256) through a heated lamination roller. The gap between the lamination rollers was subtracted from the thickness of the support membranes of L-CL and PEM1, and the value was controlled at 15μm. The hot pressing temperature was set at 150°C and the line speed was controlled at 0.5m / min to obtain L-CL-PEM.
[0220] (3) Preparation of the second catalytic layer
[0221] A second catalyst slurry is coated on the surface of L-CL-PEM to form a second catalytic layer. The obtained L-CL-PEM-CL is referred to as L-CCM. The mass ratio of solid catalyst particles, binder (solute) and dispersant in the second catalyst slurry is 1:0.5:23.5, the solid catalyst particles are carbon-supported Pt, the metal Pt content is 50wt%, the dispersant is isopropanol, and the binder is 20wt% perfluorosulfonic acid resin liquid. The TPX release film is torn off to obtain CCM.
[0222] Performance Testing
[0223] The CCM prepared in Examples 1-6 and Comparative Examples 1-2 were made into membrane electrodes and assembled into batteries, and then the battery performance under hydrogen and oxygen conditions was evaluated. Test conditions: battery operating temperature: 80°C; cathode and anode gas: H2 / Air; cathode and anode gas humidification 100RH% / 100RH%; cathode and anode initial flow 50mL / min / 50mL / min, cathode and anode metering ratio 1.5:2.5; cathode and anode outlet back pressure value 1bar. The test results are shown in Table 1.
[0224] Table 1
[0225]
[0226] It can be seen from Table 1 that compared with comparative examples 1-2, the current density of the battery of Example 1-9 is larger under the same voltage conditions, indicating that the catalyst-coated membrane prepared by the preparation method of Example 1-9 can improve the electrochemical performance of the membrane electrode and the battery. This is because the ePTFE microporous membrane, the first resin layer and the second resin layer are not deformed during the preparation process, the structure of the second catalytic layer is uniform, the first catalytic layer is tightly bonded to the surface of the first resin layer, and the surface of the membrane electrode is high in flatness and good in uniformity.
[0227] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0228] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims, and the specification and drawings may be used to interpret the contents of the claims.
Claims
1. A method for preparing a catalyst coated membrane, characterized in that: The catalyst coated membrane comprises a first catalyst layer, a first resin layer, an ePTFE microporous membrane, a second resin layer and a second catalyst layer which are stacked in sequence; and the preparation method of the catalyst coated membrane comprises the following steps: Preparing the first catalytic layer on one side surface of the release film; Prepare the first resin layer on the surface of the ePTFE microporous membrane; Laminating and pressing the first resin layer and the first catalyst layer; Preparing the second resin layer on the surface of the ePTFE microporous membrane away from the first resin layer; preparing the second catalytic layer on the surface of the second resin layer away from the ePTFE microporous membrane; The release film is removed.
2. The preparation method according to claim 1, characterized in that: The release film comprises a substrate and a release agent layer disposed on at least one surface of the substrate; Optionally, the release film is a high temperature resistant release film; Optionally, the material of the substrate includes one or more of polyethylene terephthalate, polyethylene naphthalate, polyimide and poly-4-methylpentene-1; Optionally, the material of the release agent layer includes one or more of hydroxy polypropylene resin, polycarbonate, polyurethane resin, nitrocellulose, methyl phenyl silicone resin, polydimethylsiloxane and polytetrafluoroethylene; Optionally, the first resin layer and the second resin layer each independently comprise a perfluorosulfonic acid resin.
3. The preparation method according to claim 1 or 2, characterized in that: The step of preparing the first catalytic layer on one side surface of the release film comprises the following steps: A first catalyst slurry is coated on one side of the release film, and the first catalyst layer is formed after drying; the first catalyst slurry comprises a first catalyst, a first binder and a first dispersant, and the mass ratio of the first catalyst, the solute in the first binder and the first dispersant is 1:(0.15-1):(10-36); Optionally, the first catalyst comprises one or more of carbon-supported Pt and carbon-supported Pt alloy; further optionally, the content of Pt element in the first catalyst is 20wt%-70wt%; Optionally, the first dispersant includes one or more of ethanol, methanol, isopropanol, n-propanol, n-butanol, ethylene glycol and tert-butanol; Optionally, the first binder includes perfluorosulfonic acid resin; further optionally, the mass percentage of the perfluorosulfonic acid resin in the first binder is 5wt%-25wt%; Optionally, the process conditions for coating the first catalyst slurry on one side surface of the release film include: a coating speed of 0.1 m / min-3 m / min, and a coating thickness of 30 μm-200 μm.
4. The preparation method according to claim 1 or 2, characterized in that: The step of preparing the first resin layer on one side surface of the ePTFE microporous membrane comprises the following steps: Coating a first perfluorosulfonic acid resin solution on one side surface of the ePTFE microporous membrane, and forming the first resin layer by drying; Optionally, before the step of preparing the first resin layer on one side surface of the ePTFE microporous membrane, the method further comprises: arranging a support membrane on a side of the ePTFE microporous membrane away from the first resin layer; Optionally, after the step of laminating and laminating the first resin layer and the first catalytic layer, the method further includes: removing the support film; further optionally, the material of the support film includes one or more of hydroxy polypropylene resin, polycarbonate, polyurethane resin, nitrocellulose, methylphenyl silicone resin, polydimethylsiloxane, polytetrafluoroethylene, polyethylene terephthalate, polyethylene naphthalate, polyimide and poly-4-methylpentene-1; further optionally, the thickness of the support film is 25 μm-75 μm; Optionally, the ePTFE microporous membrane has a thickness of 2 μm-15 μm, a pore size of 0.2 μm-10 μm, and a porosity of 50%-90%; Optionally, in the first perfluorosulfonic acid resin liquid, the mass fraction of the first perfluorosulfonic acid resin is 25%-50%; Optionally, the coating thickness of the first perfluorosulfonic acid resin solution is 20 μm-50 μm; Optionally, the process conditions of the drying treatment include: drying at 60°C-80°C for 0.3h-1h, and then drying at 80°C-100°C for 0.4h-1.5h; Optionally, the pressing temperature is 120°C-170°C; Optionally, the lamination line speed is 0.5m / min-1m / min.
5. The preparation method according to claim 1 or 2, characterized in that: The step of preparing the second resin layer on the surface of the ePTFE microporous membrane away from the first resin layer comprises the following steps: Applying a second perfluorosulfonic acid resin liquid on the surface of the ePTFE microporous membrane away from the first resin layer, and curing to form the second resin layer; Optionally, the curing process conditions include: a curing temperature of 150° C. to 180° C. and a curing time of 0.5 h to 1.5 h; Optionally, in the second perfluorosulfonic acid resin liquid, the mass fraction of the second perfluorosulfonic acid resin is 12%-18%; Optionally, the coating thickness of the second perfluorosulfonic acid resin solution is 30 μm-70 μm.
6. The preparation method according to claim 1 or 2, characterized in that: Preparing the second catalytic layer on the surface of the second resin layer away from the ePTFE microporous membrane comprises the following steps: Applying a second catalyst slurry on the surface of the second resin layer away from the ePTFE microporous membrane to form the second catalyst layer; The second catalyst slurry includes a second catalyst, a second binder, and a second dispersant, and the mass ratio of the second catalyst, the solute in the second binder, and the second dispersant is 1:(0.15-1):(10-36); Optionally, the second catalyst comprises one or more of carbon-supported Pt and carbon-supported Pt alloy; further optionally, the content of Pt element in the second catalyst is 20wt%-70wt%; Optionally, the second dispersant includes one or more of ethanol, methanol, isopropanol, n-propanol, n-butanol, ethylene glycol and tert-butanol; Optionally, the second binder includes perfluorosulfonic acid resin; further optionally, the mass percentage of the perfluorosulfonic acid resin in the second binder is 5wt%-25wt%.
7. The preparation method according to claim 1 or 2, characterized in that: After the step of removing the release film, the method further comprises: soaking the intermediate obtained after removing the release film in an organic solvent, and drying the organic solvent to obtain a catalyst coating film; Optionally, the organic solvent includes one or more of ethyl acetate, methyl acetate, toluene and xylene; Optionally, the infiltration time is 1 min-20 min.
8. A catalyst coated membrane, characterized in that: The catalyst coating membrane is prepared by the preparation method described in any one of claims 1-7.
9. A membrane electrode, characterized in that: It comprises at least one of the catalyst coated membranes prepared by the preparation method according to any one of claims 1 to 7 and the catalyst coated membrane according to claim 8.
10. A fuel cell, characterized in that: Comprising the membrane electrode according to claim 9.